2015
DOI: 10.4049/jimmunol.1401854
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Type 4 Cyclic Nucleotide Phosphodiesterase Blocks Intracellular TLR Signaling in Chronic Lymphocytic Leukemia and Normal Hematopoietic Cells

Abstract: A subset of chronic lymphocytic leukemia (CLL) B cell receptors (BCRs) interact with antigens expressed on apoptotic cells, suggesting that CLL BCRs have the potential to internalize apoptotic cell RNA or DNA-containing fragments with resultant activation of TLR7 or TLR9, respectively. By blocking cAMP degradation, type 4 cyclic nucleotide phosphodiesterase (PDE4) inhibitors activate cAMP-mediated signaling and induce apoptosis in CLL cells. Here we show that autologous irradiated leukemic cells induce prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…This raises the interesting possibility that levels of circulating DNA could affect drug sensitivity in these B-cell malignancies. Although CpG-ODN is often thought of as a surrogate for bacterial/viral DNA, TLR9 can be activated by cellular DNA, especially mitochondrial DNA, generated during cytolysis 28 . Large amounts of DNA have been detected in the plasma/serum of patients of various B-cell malignancies, including CLL 61,62 , with highest levels found in relapsed patient samples 61 .…”
Section: 0 Discussionmentioning
confidence: 99%
“…This raises the interesting possibility that levels of circulating DNA could affect drug sensitivity in these B-cell malignancies. Although CpG-ODN is often thought of as a surrogate for bacterial/viral DNA, TLR9 can be activated by cellular DNA, especially mitochondrial DNA, generated during cytolysis 28 . Large amounts of DNA have been detected in the plasma/serum of patients of various B-cell malignancies, including CLL 61,62 , with highest levels found in relapsed patient samples 61 .…”
Section: 0 Discussionmentioning
confidence: 99%
“…The role of cAMP is quite different in diverse types of lymphoma. PDE4 inhibitors block intracellular TLR signaling and promote apoptosis of chronic lymphocytic leukemia (CLL) cells through increasing cAMP concentration [ 112 , 113 ]. Interestingly, PDE4 inhibitors induce apoptosis in B cell CLL but not in T cell CLL or normal circulating hematopoietic cells, probably due to that PDE4 inhibitors only augment glucocorticoid receptor and cAMP levels in B cell CLL [ 114 , 115 ].…”
Section: The Roles Of Camp–pka–creb Signaling Pathway In Tumorsmentioning
confidence: 99%
“…Previously, we have shown that an SLE patient's serum (SLE1), which contains anti-Sm Ab and anti-RNP Ab (Table I), activates mouse plasmacytoid dendritic cells to induce type I IFN through FcgR and TLR7 signaling (11). RNA-containing ICs made by Sm/ RNP Ag and SLE1 serum activated PBMC to induce type I IFN (29). We used a similar approach to stimulate neutrophils from lupus patients with Sm/RNP-containing ICs ( Fig.…”
Section: Ics Activate Neutrophils From Lupus Patientsmentioning
confidence: 99%